Anak Berkebutuhan Khusus (ABK): Penanganan dan pola asuh yang tepat dapat menjadikan mereka berkembang dengan baik - Khusniyah, Syarifatul (Maliki Interdisciplinary Journal, 2023)
Children with special needs have their own challenges in life, but with the right support from their parents, family and the surrounding community, they can reach their potential and become productive members of society. This article discusses the specificities of children with special needs and the challenges they face. For parents, children with special needs can present different challenges and require special support. Support from family, community and an inclusive environment is very important to help children with special needs achieve their potential.